Percepção ambiental de estudantes do ensino fundamental sobre a caatinga - Santos, Mikaely Reis (2020)
The Caatinga is one of the Brazilian biomes that suffers most from environmental degradation caused by anthropic action and its modern civilizing process, putting its biodiversity at risk. In addition, people's ‘lack’ of knowledge about this biome and the mistaken disclosure of its image as a poor and dry environment have contributed to its devaluation and deterioration and this is worrying. Based on this assumption, the present study intends to analyze the environmental perceptions of 7th grade students about the Caatinga and its biodiversity in regions of the Coast, Agreste and Sertão of the State of Sergipe. For this, data collection was carried out in six state and municipal public schools in different regions of the state in which volunteer students produced drawings and texts about the caatinga. The collected data were submitted to the analysis of drawings with the support of the codes present in the study by Günindi (2012) which have already been adapted based on the fauna and flora of the Caatinga, presented in the book by Almeida-Cortez et al. (2007), while the analysis of descriptive texts was based on Bardin's Content Analysis (2011). As a result, among the 55 drawings and texts analyzed, 51students from Sertão, Agreste and Litoral attribute the following characteristics to Caatinga: the semi-arid climate, long periods of drought, little availability of water due to irregular rain that results in dry soil and hot, in addition to the difficulty of surviving in this environment. Although, four students (2 from Sertão, 1 from Litoral and 1 from agreste) characterize the Caatinga as humid. Students, in general, were aware of the richness of the caatinga's biodiversity. In addition, students from the agreste and the sertão pointed out the historical landmark of the “Rota do Cangaço” and the tradition “takes ox in the woods”, a cultural aspect pointed out by a student from the sertão. As for the conservation status of the biome, two students from Litoral and Sertão pointed out the anthropic changes. The results point to a naturalistic perception of the students, that is, with very little relation to the social, cultural and historical contexts in which the human presence is inserted. Thus, the awareness of each individual is necessary in addition to the implementation of Environmental Education projects aimed at the school context and rural and urban communities.